UNRAVELING THE IMPACT OF LONELINESS ON BRAIN AND EMOTION: EXPLORING PATHWAYS FOR MEANINGFUL INTERVENTIONS - Azmi, Alya Qistina Norshamsul; Ahmad Razif, Nurfahirah Irdina; Ahmad, Nur Amirah Husna; Zulkifli, Nor Wadiah; Amran, Nur Qistina Zahirah; Che Mohd Nassir, Che Mohd Nasril; Ahmed, Mohamed Ayaaz; Osman, Rahmah Ahmad; Md Tajudin, Huriyyah Hamiemah; Jaffer, Usman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This paper aims to understand and explore the complex connections between loneliness, brain functions, the emotional regulations, along with the effects of loneliness on the brain and emotions. Besides, this study is addressing its implications for mental health and potential intervention strategies. The definition of loneliness is concluded as a subjective experience of social isolation, which has profound effects on the neural processes and impaired social cognition. Key findings of this paper have highlighted the role of stress-related neuropeptides and decreased activity in emotional processing regions such as the amygdala and impaired social cognition. This paper also reviews and examines potential interventions including mindfulness practices, social cognitive training, and community training that showed promising effects on mitigating loneliness. It is further explained by the integration of physiological psychology along with Islamic perspectives to emphasize the spiritual practices, feeling of gratitude, and social bonds in fostering emotional resilience for individuals. This study emphasizes the importance of holistic approaches to convey loneliness of individuals and even at the societal levels as well as offering such valuable implications for mental health practitioners.